Analisis Yuridis Dissenting opinion Hakim dalam Sengketa Pemberhentian Tidak Hormat Anggot Polri - Aditya Afieq; Yudin Yunus; Nur Qalbi Andini (Unisan Law Review, 2026)
This study aims to analyze the juridical position of judges’ dissenting opinions in disputes concerning dishonorable discharge from the Indonesian National Police and to examine the legal reasoning underlying the dissenting opinion contained in Decision Number 12/G/2021/PTUN.GTO. This research employed normative legal research with statutory and case approaches. The findings reveal that dissenting opinion constitutes a juridical manifestation of judicial independence and serves as an academic instrument to assess the quality of judicial reasoning. In the examined case, the dissenting opinion arose from a fundamental divergence between the majority judges, who emphasized formal procedural legality, and the minority judge, who prioritized due process, proportionality, and substantive justice. This difference indicates that adjudication in state administrative disputes must not merely focus on administrative compliance, but must also ensure adequate protection of legal rights against governmental action.